👤

log3 (x – 1)² > 2 patulong po!​

Sagot :

Answer:

x < -2 or x > 4

Step-by-step explanation:

[tex]\sf log_3 (x-1)^2 > 2[/tex]

We know that [tex]\sf log_b(a) = c[/tex] is [tex]\sf a = b^c[/tex] in exponential form.

In this case, we have > instead of =.

Thus

[tex]\sf log_3 (x-1)^2 > 2 \rightarrow (x-1)^2 > 3^2[/tex]

Solving,

[tex]\implies \sf \sqrt{(x-1)^2} > \sqrt{3^2}[/tex]

[tex]\implies \sf |x-1|>3[/tex]

As per the Absolute Value Inequalities rule,

[tex]\sf If \ |a| > b, \ then \ a>b \ or \ a<-b[/tex]

Hence,

[tex]\sf x-1 > 3 \ or \ x -1 <-3[/tex]

Solving x - 1 > 3, we get x > 4.

Solving x - 1 < -3, we get x < -2.

Therefore x < -2 or x > 4

#CarryOnLearning